The Effect Of Know, Want, Learn (KWL) Strategy Towards Students’ Motivation And Writing Achievement - Tawali Tawali (Cordova Journal : languages and culture studies, 2020)
The aim of study was to find out the effect of KWL strategy towards students’ motivation and writing achievement, as well as its correlation between them.This study applied quantitatif method with experimental study type. The technique of collecting the data of the study was using Pre-test and Post-test: the test was return test and oral test. And the data analysis technique used median, mode and mean to find the coralation between students’ motivation and writing skills. based on the explanation above, the researcher concluded that know, want to learn there was any effect towards students motivation and writing achievement. Based on the data analysis, the researcher found that the result of test using ANCOVA were accepted because the result of test by used application of SPSS 24 was F-test= 14. 972 higher than F-table = 4. 09 and sig. 0,000 lower than score of alpha 0,05. This meant that the null hypothesis (Ho) which said, “KWL strategy has no positive influenced towards students’ motivation and writing achievement.” was rejected, while the alternative hypothesis (Ha) which said, “KWL strategy has positive influenced towards student Motivation and Writing Achievement” was accepted.